Potassium permanganate (KMnO_4) sensing based on microfiber sensors - Irawati, Ninik; Yusuf, Nur Atiqah M.; Rahman, Husna Abdul; Yasin, Moh; Ahmad, Harith; Harun, Sulaiman Wadi (Optical Society of America, 2017)
Two straight microfiber sensors are proposed and demonstrated for the detection of various concentrations of a potassium permanganate (KMnO4) solution. Two types of straight microfibers, namely, silica microfiber and poly(methyl methacrylate) microfiber, have been fabricated by using the flame brushing technique and the direct drawing technique, respectively. Based on the varied KMnO4 concentrations of the solution from 1% to 6%, the measurement of the peak voltage of the transmission power was made. The results show that the sensitivity of the silica microfiber sensor and the polymer microfiber is obtained at 184.5 μW/% and 32.57 μW/% with a resolution of 0.0035% and 0.0064%, respectively. Hence, the silica microfiber is more sensitive than the polymer microfiber for KMnO4 concentration measurements.